Real-time monitoring of particulate matter size, concentration, and complex index of refraction - Waez, Mir Seliman (Kansas State University, 2019)
This dissertation focuses on real-time monitoring of particulate matter concentration and sizing, and determining the complex index of refraction of single particles simultaneously. We investigated application of low-cost optical dust sensors GP2Y1010AU0F for monitoring of indoor air quality (IAQ) in buildings; developed a single-particle detector for large, non-absorbing spherical particles so the particles could be sized independently of the refractive index; and developed another sensor to determine the size and complex index of refraction of single particles simultaneously. We calibrated low-cost optical dust sensors GP2Y1010AU0F using an aerodynamic particle sizer (APS) as a reference instrument. Four sensors were connected in series with the APS and data were collected simultaneously on the downstream of a flow loop where the aerosol concentration was controlled. Sensors’ performances were compared to each other as well as to the manufacturer’s calibration data. Sensors were also exposed at two different positions in a controlled chamber to collect (1) indoor air data and (2) indoor air data with incense burning; results were compared to the calibration data. Initially, it was found that sensors’ data were different from each other by ±15%. This percentage was decreased to ±5.9% by adjusting the potentiometer on each sensor. Since the sensors work with light scattering, it was found their outputs were affected by ambient light levels causing uncertainties in the measured values. Sensors’ data for indoor air with incense burning were affected by airflow. When connected in series to the APS with 5 L/min airflow passing through them, their data agreed with the calibration data; however, they did not agree when exposed to still air i.e., without airflow. To determine the size of non-absorbing spherical particles independent of their refractive indices, we found the differential scattering cross-section to be only independent of the real refractive index at angles near 37 ± 5°. We built a device by modifying a Gaussian incident beam profile to a diamond-shaped beam so that the beam transit time of a particle passing through it could determine the true incident intensity for the scattering of the particle. By combining the modified Gaussian incident beam profile with detection of scattered light near 37 ± 5°, we demonstrated a refractive-index independent measurement of single spherical particles as they passed through the beam. In order to simultaneously determine the size and complex index of refraction of single particles, we developed a sensor that measures the scattered-light intensity of particles at three different scattering angles, i.e., 37 ± 5°, 80 ± 5°, and 115 ± 5°, in a diamond-shaped beam. The differential scattering cross-section is only independent of the real part of the refractive index at 37 ± 5°; however, in the case of absorbing particles, it depends on the imaginary part. At 115°, particles can be sized independently of the imaginary component; however, at 80°, it depends on both the real and the imaginary components. Although this dependence agrees at several angles, we have chosen 80° because the variation of the differential scattering cross-section at this angle is more consistent compared to other scattering angles.
Keywords: Particulate matter; Complex index of refraction; Particle size; Scattering angle; Light scattering